Biomechanics a case-based approach - Flanagan, Sean P. 1968- (Jones & Bartlett Learning, 2019)
"The second edition of Biomechanics: A Case-Based Approach focuses on the comprehension, retention, and application of the core concepts of biomechanics using problem-based learning strategies. Relevant and realistic problems provide students with the opportunity to associate what they're learning in class to real-life applications in the field"